2019
DOI: 10.5114/polp.2019.88040
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum vaspin concentration in full-term neonates with early-onset infections

Abstract: Aim of the study: The evaluation of serum vaspin concentration (SVC) in full-term, appropriate for gestational age (AGA) neonates, according to their sex, gestational age, anthropometric parameters, type of delivery, birth asphyxia, and kind of infection. Material and methods: In 183 full-term neonates, 102 infected and 81 healthy, 108 male and 75 female, 119 born vaginally and 64 by caesarean section, SVC was measured in serum of peripheral venous blood by ELISA test between the third and seventh day of life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition, it blocks the activation of NF-κB in endothelial and pancreatic cells, preventing the development of inflammation. By inhibiting Kallikrein 7, vaspin blocks insulin degradation, resulting in reduced insulin resistance and improved glucose tolerance [ 34 ]. In our study, we observed statistically significant differences in serum levels between patients with BMI levels indicating pre-obesity or obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it blocks the activation of NF-κB in endothelial and pancreatic cells, preventing the development of inflammation. By inhibiting Kallikrein 7, vaspin blocks insulin degradation, resulting in reduced insulin resistance and improved glucose tolerance [ 34 ]. In our study, we observed statistically significant differences in serum levels between patients with BMI levels indicating pre-obesity or obesity.…”
Section: Discussionmentioning
confidence: 99%